UPAYA PENGUATAN KEMAMPUAN BACA AL-QUR'AN BAGI LANSIA DIMASJID AR-RAHMAN DI KELURAHAN LINGKAR BARAT KOTA BENGKULU - M. Ridho Syahrini; Andre Nusprendi; M. Nadian Oky Saputra; Fiter Nurahmadi; Hanifah Muslimah (PT. Hasba Edukasi Mandiri, 2026)
Efforts to improve the ability to read the Qur'an for the elderly is an important form of religious guidance in order to improve the spiritual quality of the community. This study aims to describe the implementation of a program to strengthen the ability to read the Qur'an for the elderly at the Ar-Rahman Mosque, Lingkar Barat Village, Bengkulu City using the Qiroati method. The Qiroati method was chosen because it is considered effective in helping elderly participants understand and pronounce the hijaiyah letters properly and correctly according to the rules of tajwid. This study used a qualitative descriptive approach with a total of 10 elderly participants. The main resource person in this activity was an informant with the initials S as a teacher in the program. The results of the study indicate that the Qiroati method is able to gradually improve the ability to read the Qur'an in the elderly, despite obstacles such as limited memory and learning speed. However, with a patient approach, repetition of the material, and consistent guidance, participants showed positive developments in reading the Qur'an. This program is expected to continue as a form of religious empowerment for the elderly in the community.